2016
DOI: 10.1073/pnas.1506012113
|View full text |Cite
|
Sign up to set email alerts
|

Convergent evidence from alcohol-dependent humans and rats for a hyperdopaminergic state in protracted abstinence

Abstract: A major hypothesis in addiction research is that alcohol induces neuroadaptations in the mesolimbic dopamine (DA) system and that these neuroadaptations represent a key neurochemical event in compulsive drug use and relapse. Whether these neuroadaptations lead to a hypo-or hyperdopaminergic state during abstinence is a long-standing, unresolved debate among addiction researchers. The answer is of critical importance for understanding the neurobiological mechanism of addictive behavior. Here we set out to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
131
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 67 publications
9
131
0
1
Order By: Relevance
“…As increased glutamatergic excitability is observed during withdrawal periods (Wang et al, 2010), thus it is plausible that glutamatergic signaling contributes to the activation of this pathway in the NAc shell and/or OFC. Interestingly, Hirth et al recently demonstrated a hyperdopaminergic state during protracted abstinence, showing that opposite dynamical changes take place in the mesolimbic dopaminergic system in alcohol acute withdrawal and protracted abstinence (Hirth et al, 2016). It would be of interest to test the activation of AKT/mTORC1 signaling pathway after a longer period of abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…As increased glutamatergic excitability is observed during withdrawal periods (Wang et al, 2010), thus it is plausible that glutamatergic signaling contributes to the activation of this pathway in the NAc shell and/or OFC. Interestingly, Hirth et al recently demonstrated a hyperdopaminergic state during protracted abstinence, showing that opposite dynamical changes take place in the mesolimbic dopaminergic system in alcohol acute withdrawal and protracted abstinence (Hirth et al, 2016). It would be of interest to test the activation of AKT/mTORC1 signaling pathway after a longer period of abstinence.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with AUDs report a broad range of alcohol consumption, between 0.7g/kg/day and ≥ 3.9g/kg/day (Hietala et al, 1994; Hirth et al, 2016; Volkow et al, 2002; Wang et al, 2016). In addition, while some individuals establish chronic heavy drinking behavior, others maintain chronic, lower levels of consumption, and still others develop binge-drinking patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Hirth et al (2016) showed a strong down-regulation of the D1 receptor- and dopamine transporter-binding sites in postmortem brain samples from human alcoholics. Furthermore, many genetic studies have demonstrated an association of variants in SLC6A3 with addiction-related behaviors (Ma et al, 2015b, van der Zwaluw et al, 2009) and neuropsychiatric disorders (Gill et al, 1997, Cornish et al, 2005).…”
Section: Discussionmentioning
confidence: 99%